The H-D-isotope effect of heavy water affecting ligand-mediated nanoparticle formation in SANS and NMR experiments - Krauss, Sebastian W.; Eckardt, Mirco; Will, Johannes; Spiecker, Erdmann; Siegel, Renée; Dulle, Martin; Schweins, Ralf; Pauw, Brian; Senker, Jürgen; Zobel, Mirijam (Nanoscale, 2023)
An isotopic effect of normal (H2O) vs. heavy water (D2O) is well known to fundamentally affect the structure and chemical properties of proteins, for instance. Here, we correlate the results from small angle X-ray and neutron scattering (SAXS, SANS) with high-resolution scanning transmission electron microscopy to track the evolution of CdS nanoparticle size and crystallinity from aqueous solution in the presence of the organic ligand ethylenediaminetetraacetate (EDTA) at room temperature in both H2O and D2O. We provide evidence via SANS experiments that exchanging H2O with D2O impacts nanoparticle formation by changing the equilibria and dynamics of EDTA clusters in solution as investigated by nuclear magnetic resonance analysis. The colloidal stability of the CdS nanoparticles, covered by a layer of [Cd(EDTA)]2− complexes, is significantly reduced in D2O despite the strong stabilizing effect of EDTA in suspensions of normal water. Hence, conclusions about nanoparticle formation mechanisms from D2O solutions reveal limited transferability to reactions in normal water due to isotopic effects, which thus need to be discussed for contrast match experiments.
CRIS-Team Scopus Importer:2023-11-10